Durable clinical benefit from gefitinib plus bevacizumab in a non-small cell lung cancer patient with an acquired C797S mutation following osimertinib treatment: a case report and literature review - Tan, Yuping; Dong, Meng; Li, Xi; Li, Wenbo; Xiong, Fei; Bao, Weidong; Dai, Yongzhou; Yue, Linjun; Liu, Yuan (Frontiers in Oncology, 2025)
BackgroundThe emergence of the epidermal growth factor receptor (EGFR) C797S mutation in the absence of T790M represents a common mechanism of acquired resistance to first-line osimertinib in non-small cell lung cancer (NSCLC), posing a significant clinical challenge.Case presentationWe present the case of a 72-year-old man diagnosed with metastatic NSCLC harboring an EGFR exon 19 deletion who developed an acquired C797S mutation (without T790M) following 25 months of first-line osimertinib therapy. Based on this molecular profile, the patient received a regimen of gefitinib combined with bevacizumab. This combination was well tolerated and resulted in a partial response, achieving a progression-free survival (PFS) of 15.5 months.ConclusionThis case indicates that the combination of gefitinib and bevacizumab may offer a durable clinical benefit for NSCLC patients who develop osimertinib resistance via the C797S mutation. The observed outcomes warrant further investigation into this dual-blockade strategy, especially given the limited duration of response noted for tyrosine kinase inhibitor (TKI) monotherapy.